1999
DOI: 10.1128/aac.43.3.678
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Renal Failure on Intestinal Clearance of Ciprofloxacin in Rats

Abstract: Following intravenous doses, ciprofloxacin pharmacokinetics in control and nephrectomized rats were studied. There were no differences between control and nephrectomized rats for area under the concentration-time curve in plasma or biliary clearance. The intestinal clearance of ciprofloxacin was increased in nephrectomized rats. Intestinal elimination seems to compensate partially for the decrease in urinary excretion of ciprofloxacin in nephrectomized rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Forrest et al [20] found a significant relationship between total ciprofloxacin clearance and CL Cr estimated by the Jelliffe formula, mostly in patients with lower respiratory tract infection. Additionally, when ciprofloxacin renal clearance is compromised, the transintestinal elimination route is frequently described in the literature in humans and animals as the main compensatory elimination route [38][39][40]. In septic patients, Jones et al [39] showed that only those patients who had liver or bowel pathology in addition to renal failure had a significantly higher serum concentration than all other patients.…”
Section: Discussionmentioning
confidence: 99%
“…Forrest et al [20] found a significant relationship between total ciprofloxacin clearance and CL Cr estimated by the Jelliffe formula, mostly in patients with lower respiratory tract infection. Additionally, when ciprofloxacin renal clearance is compromised, the transintestinal elimination route is frequently described in the literature in humans and animals as the main compensatory elimination route [38][39][40]. In septic patients, Jones et al [39] showed that only those patients who had liver or bowel pathology in addition to renal failure had a significantly higher serum concentration than all other patients.…”
Section: Discussionmentioning
confidence: 99%
“…Enteral and hepatic elimination are obviously enhanced when renal clearance is reduced (7, 24). Dose reduction for patients with renal insufficiency and coexistent bowel/liver diseases has been recommended (16).…”
Section: Discussionmentioning
confidence: 99%
“…They are localized at the apical membrane of cells like P‐gp ( Tsui & Tamai, 1996 ) or at the basolateral membrane like OCT‐1 ( Zhang et al ., 1998 ). For this reason, in order to study the mechanism(s) involved in its intestinal elimination, ciprofloxacin was administered parenterally at a dose of 12.5 mg kg −1 (a dose which is compatible with a linearity of biliary and intestinal kinetics [ Dautrey et al ., 1999 ]) alone, and in the presence of different compounds potentially capable of interacting with it. These compounds were administered parenterally 15 min before ciprofloxacin in order to optimize diffusion into the different organs.…”
Section: Discussionmentioning
confidence: 99%